Geological Conditions and Sedimentary Models of Oligocene and Eocene Effective Source Rocks in the Northern Yinggehai Basin - Jianxiang Pei; Gaowei Hu; Zhipeng Huo; Zhihong Chen; Yabing Chen; Xiaofei Fu; Weihong Wang; Haiyu Liu; Yanan Wang; Jingshuang Luo; Guofei Chen (Journal of Marine Science and Engineering)
The development of the effective source rocks of the Eocene and Oligocene directly determines the oil and gas exploration potential in the northern Yinggehai Basin in China. Based on the analogy with the Hanoi Depression in Vietnam and the Yacheng District in the Qiongdongnan Basin and the comprehensive analysis of self-geological conditions, the development conditions of Eocene and Oligocene source rocks in the northern Yinggehai Basin are examined, focusing on tectonic evolution, sedimentary facies, and the paleoenvironment. Finally, the sedimentary models for the effective source rocks are established. The tectonic activity controlled the formation of the sedimentary deep depression and the migration of the sedimentary trough center, which migrated from east to west and then south from the Eocene to the Oligocene, leading to the sedimentary migration of good muddy source rocks. There are multiple sedimentary facies in favor of source rocks, including lacustrine facies, shallow marine facies, and delta plain swamps. The paleoenvironment indicates that the paleoclimate transitioned from warm and humid to cold and arid, the redox conditions evolved from semi-reducing to oxic, and paleoproductivity increased from the early to late Oligocene. Therefore, the early Oligocene was more conducive to the enrichment of organic matter. It is speculated that the warm and humid paleoclimate, reducing environment, and high paleoproductivity of the Eocene promoted the sedimentation and preservation of more organic matter. The above studies show that the northern Yinggehai Basin, especially the sedimentary period of the Eocene and Oligocene, has favorable geological conditions for the development of effective source rocks. The sedimentary models for Eocene lacustrine mudstones and Oligocene marine mudstones and marine–continental transitional coal-measure source rocks were established. These studies make up for the serious deficiency of previous research and mean that there is great exploration potential for oil and gas in the northern Yinggehai Basin in China.